Differential Infiltration of Immune Cells Driven by Tumor Heterogeneity Reveals Two Immune Subtypes in Lung Adenocarcinoma - Wang, Liqiang; Song, Ying; Bai, Jing; Sun, Wenjing; Yu, Jingcui; Cai, Mengdi; Fu, Songbin (Frontiers in Genetics, 2022)
Intra-tumoral heterogeneity (ITH) is a critical factor leading to aggressive progression and response to immunotherapy in lung adenocarcinoma (LUAD). However, the relationship between ITH and immune cells in tumor microenvironment has not been systematically elucidated. In the present study, we evaluated the ITH status of LUAD samples based on the mutational data obtained from The Cancer Genome Atlas (TCGA) database. Firstly, we identified five key immune pathways with significantly continuous downtrend among normal, low heterogeneous and high heterogeneous samples, and further excavated nine key immune cells related to the key immune pathways and tumor heterogeneity. Then, two immune subtypes were defined by consensus clustering algorithm based on the infiltration of these immune cells. Differences between these two immune subtypes were remarkable, including alterations of tumor mutation burden (TMB) and DNA copy number variation (CNV) at the genomic level, various metabolic profiling, and the different clinical outcome which was also validated in two independent Gene Expression Omnibus (GEO) datasets. The results revealed that ITH was significantly associated with prognosis and infiltrating immune cells in tumor microenvironment. Our study provides novel insights in understanding the relationship between ITH and immune cells and contributes to the immunotherapy of LUAD patients.